Designing imminent threat messages for an unfamiliar hazard. Issue 4 (2nd October 2018) - Sutton, Jeannette N.; Kaufmann, Renee
Abstract : Course: This assignment is a unit activity designed for use in a skills-focused undergraduate public relations, organizational communication, or crisis communication course. Objective: The goal of this activity is to increase students' understanding and ability to apply message design concepts in an unfamiliar context. Students will work collaboratively to craft messages that include key message features in response to an unfamiliar threat.